OP I – 5 Prenatal and postnatal exposure to air pollution and white matter microstructure in school-age children. (18th March 2018) - Lubczyńska, Gosia; Marroun, Hanan El; Muetzel, Ryan; Strak, Maciej; Denault, William; Hoek, Gerard; White, Tonya; Brunekreef, Bert; Tiemeier, Henning; Guxens, Mònica
Abstract : Background/aim: Exposure to air pollution is related to brain structural variations but the relationship with white matter microstructure has not yet been established. Here, we aimed to assess whether pre- and postnatal exposure to a wide range of different air pollutants is related to white matter microstructure in school-age children. Methods: We used data from 2977 children aged 8–12 years from a birth cohort in Rotterdam, The Netherlands (2002–2006). Concentrations of nitrogen oxides, particulate matter (PM) and various components of PM were estimated at home addresses using land-use regression models for the entire prenatal period and from birth until the visit at the research centre. Diffusion tensor images were obtained during the magnetic resonance imaging session and fractional anisotropy (FA) and mean diffusivity (MD) values were computed. Deletion/substitution/addition algorithm was used to select the most predictive pollutants accounting for the covariance between them. The selected pollutants were then related to white matter microstructure, adjusting for various parental socioeconomic and life-style characteristics. Results: Overall, exposure to several air pollutants was associated with decreases in FA values and increases in MD values, which possibly indicate brain alterations. These results were consistent for both pre- and postnatal air pollution estimations, yet more profound with postnatal exposures (e.g. a decrease in FA of 0.41 [95% Confidence Interval CI: −0.78 to −0.04] and an increase in MD of 0.05 [95% CI: 0.01 to 0.10] for each 1 ng/m 3 increase in polycyclic aromatic hydrocarbons (PAHs) during childhood). Conclusion: Exposure to various air pollutants during fetal life and childhood was associated with alterations in white matter microstructure in school-age children. Previous studies show that lower FA and higher MD values are associated with psychiatric and neurological disorders. Considering the ubiquity of the exposure, these results raise concern and point out the need for further research in this area.